Error Analysis of Grammar Mastery by the First Semester Students of Hospital Administration at IIK Bhakti Wiyata Kediri - PALUPI SUSILOWATI; YENI NURMALA HIDAYATI (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2023)
To improve students’ language ability, grammar is a crucial language element. While writing their essays, many students still commit grammatical mistakes. This study was run in the first semester students of Hospital Administration, Faculty of Health in the 2022/2023 academic year, which aimed at: 1. Finding out the types of common errors in composing sentences, 2. Finding out the causes of errors. The method applied in this research was error analysis, through these steps: 1. Identifying data of errors 2. Classifying errors based on theory of grammar 3. Analyzing errors. The data were taken by conducting a multiple-choice test about completing sentences with the right grammar construction. The data were analyzed with qualitative method. The result showed that there were errors in composing sentence with Modal Verbs, Adverb, Reported Speech, Preposition and Conditional Sentence. Those common errors were caused by both inter-lingual and intra-lingual references.